A Decade of Improvement in Door‐to‐Puncture Times for Mechanical Thrombectomy But Ongoing Stagnation in Prehospital Care - Chung‐Huan Sun; Osama O. Zaidat; Alicia C. Castonguay; Erol Veznedaroglu; Ronald F. Budzik; Joey English; Blaise Baxter; Raul G. Nogueira; Antonín Krajina; Bruno Bartolini; David S. Liebeskind; Wade Smith; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background Systems of care surrounding endovascular therapy for stroke have garnered much attention in recent years. In‐hospital metrics, such as “door‐to‐puncture” and procedure times have been areas for quality improvement. The temporal trend and clinical significance of prehospital “onset‐to‐door” time, however, remains unknown. Methods We performed a systematic review of time metric data from all published randomized controlled and investigational device exemption trials involving endovascular therapy for stroke between 2005 and 2019 (n=26). Second, we conducted a record‐level observational analysis on a total of 3512 patients from 3 real‐world registries (Mechanical Embolus Removal in Cerebral Ischemia [MERCI], Thrombectomy REvascularization of Large Vessel Occlusions in Acute Ischemic Stroke [TREVO], and TREVO Stent‐Retriever Acute Stroke [TRACK]), together with 4 prospective trials (MERCI trial, Multi‐MERCI, TREVO‐EU, and TREVO‐2). Only patients receiving mechanical thrombectomy within 9 hours from onset‐to‐puncture time were included. Predictors of good outcome were identified using generalized linear mixed modeling. Results Door‐to‐puncture times (slope=−5.83 min/y; R2=0.25; P=0.046), procedure times (slope=−3.78 min/y; R2=0.54; P<0.001), and onset‐to‐reperfusion times (slope=−11.82 min/y; R2=0.57; P<0.001) improved over the years among previously published randomized controlled trials/investigational device exemption trials from 2005 to 2019. The prehospital metric of onset‐to‐door time, however, remained statistically unchanged (slope=1.03 min/y; R2<0.01; P=0.806). Pooled analysis from record‐level data demonstrated a similar temporal trend where door‐to‐puncture, procedure, and onset‐to‐reperfusion times declined by an average of 12 minutes (R2=0.45; P<0.0001), 6 minutes (R2=0.27; P<0.0001), and 8 minutes per year (R2=0.18; P<0.0001), respectively, over a similar time period. Time from onset to door, however, did not improve (3.6 min/y; R2=0.34; P=0.005). In a backward‐selection regression model, onset‐to‐door time was found to be a significant predictor of patient outcomes, where every hour delay in hospital arrival correlated with a 14% reduction in the odds of a good outcome. Conclusions “Door‐to‐puncture” and procedure times have seen significant improvements over the past decade. The prehospital component of “onset‐to‐door” time, however, has remained stagnant. This presents an unrealized opportunity to enhance patient outcomes through improved systems of care in the prehospital setting.